Variability in Recommendations for Cervical Lymph Node Pathology for Staging of Canine Oral Neoplasia: A Survey Study - Congiusta, Michael; Lawrence, Jessica; Rendahl, Aaron; Goldschmidt, Stephanie (Frontiers in Veterinary Science, 2020)
There is no clear guideline regarding the indication for routine lymph node extirpation and pathologic evaluation during staging of canine oral tumors, despite a relatively high nodal metastatic rate for select tumor types. It is particularly unclear if clinicians recommend removal of lymph nodes only when there is confirmation of metastasis, defined as the N+ neck, or if elective neck dissection (END) is routinely recommended to confirm the true pathologic metastatic status of lymph nodes in the clinical N0 neck (no evidence of metastasis on clinical staging with diagnostic imaging or cytology). When clinicians are recommending END as a staging tool to confirm nodal status, there is also ambiguity regarding the surgical extent for subsequent histopathologic evaluation. The objective of this cross-sectional survey study was to determine the current recommendations given by practicing specialists regarding lymph node removal for dogs with oral tumors. Overall, 87 responses were obtained from 49 private practices (56%) and 38 academic institutions (44%). Responders identified as oncologists (44%, N=38), soft tissue surgeons (40%, N=35), and dentists (16%, N=14). Regardless of tumor type and stage, extirpation and histopathology were most commonly recommended in the clinical N+ neck only. The recommendation to routinely perform END in the N0 neck was significantly associated with tumor type. Bilateral removal of the mandibular and retropharyngeal lymph nodes was recommended more often for oral malignant melanoma (OMM) than for oral squamous cell carcinoma (OSCC; p ≤ 0.0039) or for oral fibrosarcoma (OFSA; p ≤ 0.0007). The likelihood of recommending END increased with increasing tumor size. Academic clinicians were significantly (p < 0.01) more likely to recommend END compared to private practitioners for canine T1-T3 OMM, T3 OSCC, T2 OFSA, and MCT. This study highlights the variability in recommendations for lymph node pathology for dogs with oral tumors. While tumor type and size influenced the decision to pursue END, it was not routinely recommended, even for tumor types with a propensity for metastasis. Prospective studies are warranted to determine the potential diagnostic and therapeutic value of END in the N0 neck in veterinary patients such that a consensus approach can be made.